Cover Picture: Enzymatic Synthesis of 7′, 5′‐Bicyclo‐DNA Oligonucleotides (Chem. Asian J. 12/2017). Issue 12 (5th June 2017) - Diafa, Stella; Evéquoz, Damien; Leumann, Christian J.; Hollenstein, Marcel
Abstract : Going bicyclo ! A nucleoside triphosphate analogue based on the bicyclo‐DNA architecture (7', 5'‐bc‐TTP) was synthesized, and its potential to serve for the generation of new xenonucleic acids (XNAs) was assessed. When used with the Therminator DNA polymerase, up to seven modified 7', 5'‐bc‐nucleotides could be incorporated into DNA. In addition, this scaffold also supports XNA‐dependent DNA synthesis as well as potentially XNA‐dependent XNA synthesis, and thus represents a candidate for the generation of novel synthetic genetic polymers. More information can be found in the Communication by Christian Leumann, Marcel Hollenstein et al. onpage 1347 in Issue 12, 2017 (DOI:10.1002/asia.201700374 ).